The intragenic epistatic association of ADD3 with biliary atresia in Southern Han Chinese population. Issue 3 (12th June 2018) - Wang, Zhe; Xie, Xiaoli; Zhao, Jinglu; Fu, Ming; Li, Yonglan; Zhong, Wei; Xia, Huimin; Zhang, Yan; Zhang, Rui-Zhong
Abstract : Biliary atresia (BA) is a multifactorial pathogenic disease with possible genetic components. As a member of membrane skeletal proteins in the liver and bile ducts, a haplotype composed by five single nucleotide polymorphisms (SNPs) on adducin 3 ( ADD3 ) has been identified as associated with BA. However, limited study was designed to further elaborate the mutual relationship amongst those replicated SNPs to disease. We selected three susceptibility SNPs in ADD3 and conducted a replication study using 510 BA cases and 1473 controls to evaluate the individual function of the SNPs and further stratified the potential roles with disease and its subclinical features. Two SNPs in ADD3 were replicated as associated with BA (1.60E-04 ≤ P ≤1.70E-04, 1.33 ≤ odds ratio (OR) ≤ 1.58 for rs17095355, 2.10E-04 ≤ P ≤5.30E-04, 1.26 ≤ OR ≤ 1.57 for rs2501577). Though we failed to replicate the individual association of rs10509906 to disease, the intragenic epistatic effect between rs10509906 and rs2501577 was suggested as exhibiting susceptibility to BA, further cross-validated by multifactor dimensionality reduction (MDR) ( P =0.068, OR = 1.37), which may explain extra hidden heritability of ADD3 to BA. Furthermore, through subclinical stratification, we also observed the association of risk to disease mainly came from the female patients.